Studying KcsA Channel Clustering Using Single Channel Voltage-Clamp Fluorescence Imaging* - McGuire, Hugo; Blunck, Rikard (Frontiers in Physiology, 2022)
Oligomerization and complex formation play a key role for many membrane proteins and has been described to influence ion channel function in both neurons and the heart. In this study, we observed clustering of single KcsA channels in planar lipid bilayer using single molecule fluorescence, while simultaneously measuring single channel currents. Clustering coincided with cooperative opening of KcsA. We demonstrate that clustering was not caused by direct protein-protein interactions or hydrophobic mismatch with the lipid environment, as suggested earlier, but was mediated via microdomains induced by the channel in the lipid matrix. We found that single channel activity of KcsA requires conically-shaped lipids in the lamellar liquid-crystalline (Lα) phase, and the need for a negative spontaneous curvature seem to lead to the deformations in the membrane that cause the clustering. The method introduced here will be applicable to follow oligomerization of a wide range of membrane proteins.